Bibliometric Analysis: Financial Literacy and Financial Behavior - Sri Wahyuni; Refni Sukmadewi; Setiawati Setiawati (eCo-Buss, 2022)
Currently, there is no comprehensive scientific study of financial literacy and behavior. This is due to the presence of no trends in the field of research; instead, many exploratory, conceptual and empirical studies have been carried out. The current study intends to acquire trends by synthesizing different knowledge structures. A scientific search was performed to gather data for financial literacy and financial behavior. After searching Dimensions, a web-based software application created in the R language was used to gather information automatically. This software is part of a package called Bibliometrix, which also includes a web-based application called Biblioshiny. The two are used to find sources, countries, journals, authors, articles and themes. Analysis of social networks and joint quotations are also performed using automated workflows in the software. This study involved collecting data from 417 documents. Initially, this interdisciplinary field focused on the specific aspects of demographics and socio-economic status. However, as time progressed, it expanded to include behavioral aspects and even mental concepts that affected financial behavior. The study also outlines how the field’s intellectual and social ideas combine. This study uses bibliometric analysis to study important subjects. Because of this, future researchers can use its limitations to shape their ideas. Studying the literature through a systematic review will help lead to a more solid understanding of the material. Due to Dimensions' larger scope than journals, current studies utilize the database for science mapping. This information provides important data regarding financial literacy and behaviors. It also highlights the most important issues currently being addressed in the field. This data helps lead to future research projects that focus on new areas. This paper reveals the social and intellectual foundations of a particular academic or scientific field. It also details the collaborations, contexts and key themes that emerge in this particular field. After reading this paper, other researchers can make informed decisions about financial education and financial literacy policies. A large amount of work from different fields have been done across the country. This includes work from psychology, finance, economics and other fields. The study pulls apart the current literature and unites it into one cohesive body. It also explores how behavior and financial literacy are connected